Optimization of Energy Aware Path Routing Protocol in Wireless Sensor Networks - M. Naga Vamsi Krishna; N. Sai Harsha; K.V.D Kiran; Gandharba Swain (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Strength conservation is one of the biggest challenges to the successful WSNs since the tiny  very limited resource nodes  such as energy, memory space| as well as communication and computation capabilities. the sensors are unattended Implemented  and battery recharge is almost impossible. So  many investigations have be done in redirecting energy efficient algorithms or protocols for WSNs. Our reasons behinds the study of number is based on the following three aspects. Initially of all First, we see That immediate transmittal is employed under small scale while multi-hop network transmittal network is employed under mass. All of us want to find the Which factors influence the transmittal manner. Second, it is Commonly That multi-hop agree transmitting more energy efficient than Usually transmitting When the average solitary source to destination distance is large. Yet ,}how to look for the optimal hop number in order That the overall energy consumption is  nominal is not well  tackled. Third, the hot location phenomenon the networking lifetime influences directly. After that all of us recommend to Optimization of energy aware routing path (OEAPR) algorithm, Which incorporate the overall routing mechanism With hop-based direction-finding nature During process in WSNs.